Pessoa, personalidade e intransmissibilidade dos direitos de personalidade: proposta para fundamentação da tutela post mortem - Weiszflog, Heloísa Cardillo (2016)
The object of this research was the study of the individual and the entity, when the rights of such personalities are concerned, their main feature: non-transferability. Concerning the individual, the starting point was an ontological view that, according to its understandings, grants more strength to the individual’s technical meaning. Thus, it is concluded that the best point of view to reveal such meaning is the one granting the individual material meaning, comprising, in its roots, the human being and their inherent dignity. Regarding the entity feature, the same line of thought was conducted in the research and therefore, the idea defended was that the legal entity is nothing more than the result of the anthological personality from the human being. It must be evaluated, consequently, not only as a legal trait but also as an axiological quid of compulsory recognition by the legal framework. As to the individual’s right, the research highlighted the object by which the individual is referred to, stating that such characteristic, together with powerful doctrine, is found not in the person but in the human nature as a whole. With regard to the non-transferability, there was the concern of presenting its fundaments as they shall be seen; the same as the objects before mentioned, and also the organic format in which we present the entity’s rights in relation to the owner. Then, after preparing the basis to handle the concept of post mortem injunction relief of certain entities’ rights (better yet, its emanations), some pages have been reserved to elaborate on how the practice really takes place. It is vital to clarify that the object of this paper was not to deal with post mortem injunction relief itself, although the hard matter was partially dealt, however difficult it may have been, for reasons of intellectual responsibility, offering a simple attempt of achieving a mere conclusion on the subject, as it falls far from this very overview. In sum, the issues of individuals, entities and the non-transferability of rights from these personalities present themselves as a proposal of competent premises for the setting up of a dogma aiming at effectively reaching the complexity of a theme that involves, in the last resort, what remains from those who have passed away